Experiences in managing arteriovenous malformations of the head and neck. Issue 6 (July 2016) - McMillan, Kevin; Dunphy, Louise; Nishikawa, Hiroshi; Monaghan, Andrew
Abstract: Arteriovenous malformations of the head and neck are difficult to treat and require a multidisciplinary approach. Interventional radiology can now be used to downgrade previously inoperable lesions to enable ablation, and the use of Onyx® (Covidien, Irvine, CA, USA), which has revolutionised their management by allowing precise obliteration of the nidus, has enabled the aggressive management of lesions in compromised anatomical areas. We report a series of 31 patients with lesions on the head and neck. They all presented with serious symptoms (Schobinger grade 2-3) and had embolisation with Onyx®. Some had additional operations. We describe the outcome including complications, and offer some lessons learned from our experience.